Arab Digital Academic Content Industry Weakness factors and ways to develop it - abbes, fathi; bensebti, abed malek (Journal of Social Sciences and Humanities, 2021)
The digital information content industry is among the important projects for societies to enter the information society and the knowledge society, and the digital content for scientific research is the most important source of the research process in the global evaluation of universities, and therefore it is difficult to objectively evaluate universities in the field of providing digital content due to the lack of scientific and research production in a digital way Published on the official websites of these universities, despite the availability of this scientific and research production in paper form to faculty members. Therefore, many universities have taken effective measures to improve the Arab digital content for scientific research by adopting a training matrix for faculty members to raise awareness and train on mechanisms for raising full research with the aim of making scientific content digitally available on modern means, foremost of which is social networking, which increases access to opportunities from society Academic internal and external and raises the number of reference citations to this research, and many universities have encouraged and motivated faculty members to register on the Google Scholar website to expand the availability of visibility for this scientific research so countries are striving to Its digital content on the World Wide Web, and academic academic information content produced within university institutions is among the important fields for developing the Arab digital information content industry, as these academic institutions provide professors and researchers with the opportunity to publish their work and research in scientific journals and participate in national and international conferences, and this study aims To know what the Arab academic information content industry is, the reality of this industry, as well as the reasons for its weakness and procedures for its development. The study concluded that the Arab digital content is characterized by weakness, due to various factors, including the general weakness in the structure of research and development in Arab countries and the absence of an Arab strategy for the manufacture of information content.